Phytochemical and Biological Activity Studies of Hedyotis Herbacea, Hedyotis Diffusa and Roots of Garcinia Atroviridis - Permana, Dharma (2002)
A new anthraquinone, 2-hydroxymethyl-10-hydroxy-1, 4-anthraquinone (9) was isolated from the dried aerial part of Hedyotis herbacea (Rubiaceae) together with five other known compounds, 1,4-dihydroxy-2-hydroxymethylantbraquinone (10), 2,3-dimethoxy-9-hydroxy-l,4-anthraquinone (11), 1,4-dihydroxy-2,3- dimethoxylanthraquinone (12), kaempferol 3-0-rutinose (13) and arbutin (14). Extraction and isolation of the constituents from Hedyotis diffusa has yielded three compounds, quercetin 3-0-glucose (15), quercetin 3-0-rutinose (16) and asperuloside (17). Three new prenylated compounds, the depsidone atrovirisidone (24), the benzoquinone atrovirinone (25) and the hydro quinone 4-methyldihydroatrovirinone (26), along with three known compounds, 14-cis-docosenoic acid (27), morelloflavone (28) and fukugiside (29) have been isolated from the ethyl acetate fraction of the methanol crude extract of the dried roots of Garcinia atroviridis. In the biological activity assay, quercetin 3-0-glucose (15), quercetin 3-0- rutinose (16), atrovirisidone (24), morelloflavone (28) and fukugiside (29) were found to have stronger antioxidant activity than vitamin E. 2-hydroxymethyl-lOhydroxy- l,4-anthraquinone (9) and quercetin 3-0-rutinose (16) showed strong toxic activity in the brine shrimp lethality assay with a 50 % lethal concentration of 9.7 µg/mL and 23. 4 µg/mL, respectively. Atrovirisidone (24) and atrovirinone (25) were very effective against the microbe Bacillus subtilis (mutant type) and Bacillus subtilis (wild type) (MID 10 Ilg/disc for both). Quercetin 3-0-glucose (15), quercetin 3-0-rutinose (16), 4-methyl-dihydroatrovirinone (26), morelloflavone (28) and fukugiside (29) showed weak activity compared to atrovirisidone (24) and atrovirinone (25) but it is still significantly active (MID 100 µg/disc for all compounds). Only atrovirisidone (24) exhibited cytotoxic activity towards HeLa cells at IC₅₀ 15 µg/mL that was comparable to the standards doxorubicin (IC₅₀ 11 µg/mL) and colchicine (IC₅₀ 21 µg/mL).